High Expression of DC-STAMP Gene Predicts Adverse Outcomes in AML - Liang, Qian; Zhang, Lele; Wang, Wenjun; Zhao, Jingyu; Li, Qiaoli; Pan, Hong; Gao, Zhen; Fang, Liwei; Shi, Jun (Frontiers in Genetics, 2022)
Acute myeloid leukemia (AML) is a genetically heterogeneous hematological malignancy with poor prognosis. We explored the RNA sequence data and clinical information of AML patients from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) database to search the core molecular for prognosis. The DC-STAMP expression was significantly higher in AML patients, which was linked to older age, unfavorable cytogenetic risk, and death events (all P<0.05). Furthermore, it was revealed that high DC-STAMP expression was an independent unfavorable factor for overall survival (OS) by univariate analysis (hazard ratio [HR]: 2.683; 95% confidence interval [CI]:1.723-4.178; P <0.001) and multivariate analysis (HR: 1.733; 95% CI: 1.079-2.781; P =0.023). The concordance index (C-index 0.734, 95% CI: 0.706-0.762), calibration curves, and decision curve analysis curves showed the certain predictive accuracy of nomogram model based on multivariate analysis for OS. In addition, we found the differentially expressed genes (DEGs) enrichment pathways of high- and low- DC-STAMP expression groups enrichment pathways were focused on channel activity and platelet alpha granule by gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG), while gene set enrichment analysis (GSEA) pathways mainly involved in mTORC1 signaling, TNF-α signaling via NF-kB pathway. Moreover, Protein-Protein interaction (PPI) network demonstrated that DC-STAMP interacted with two hub genes (PPBP and PF4), which were highly regulated and associated with worse survival. Finally, high DC-STAMP expression showed significantly positive correlation with four immune cells (NK CD56 (dim) cells, Macrophages, Cytotoxic cells and CD8 (+) T cells) infiltration and high level of immune checkpoint genes (PDCD1, CD274, CTLA-4 and TIGIT). Therefore, our results suggest that high expression of DC-STAMP predicts adverse outcomes of AML patients.